Pengembangan Media Pembelajaran Bahasa Indonesia Berbasis Visual untuk Meningkatkan Kemampuan Menulis Deskripsi Siswa Sekolah Dasar - Atrianing Yessi Wijayanti; Ridha Sarwono (Faculty of Teacher Training and Education of Undaris, 2023)
Writing descriptive texts is one of the essential competencies in Indonesian language learning at the elementary school level because it supports students' literacy development. However, conventional teaching methods often limit students' ability to generate ideas, enrich vocabulary, and describe objects systematically. This study aims to develop a visual-based learning media that is valid, practical, and effective in improving elementary school students' descriptive writing skills. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were 30 fourth-grade elementary school students. Data were collected through expert validation sheets, teacher and student response questionnaires, and descriptive writing tests. The findings indicate that the developed media achieved excellent feasibility with material expert validation of 92.5% and media expert validation of 94.1%. The implementation results revealed a significant improvement in students' descriptive writing skills, with the average score increasing from 68.40 in the pretest to 84.73 in the posttest. Teachers and students also provided very positive responses toward the learning media. Therefore, the developed visual-based learning media is considered feasible, practical, and effective for improving descriptive writing skills in Indonesian language learning at the elementary school level.Keywords: learning media, visual media, Indonesian language, descriptive writing, elementary school